2007
DOI: 10.3200/jach.55.6.325-332
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of a Technology-Based Social Norms Intervention to Deter Alcohol Use in Freshman Residence Halls

Abstract: Qualitative findings suggest the intervention had an overall positive impact, but the actions of a subgroup of rebellious drinkers might have obscured the effect. Social norms interventions could provoke some episodes of excessive drinking in students who find these messages objectionable. More research is needed to evaluate delayed BAC feedback.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…As shown in the second column of Table 2, social learning (cognitive) theory (Patten et al, 2006;Patten et al, 2007;Suminski & Petosa, 2006), the transtheoretical model (Escoffery, McCormick, & Bateman, 2004), the informationmotivation-behavioral skills model (Barak & Fisher, 2003), self-regulation theory, and the theoretical fields of social support (Escoffery et al, 2004;Marks et al, 2006) and social norms (Saitz et al, 2007;Thombs et al, 2007) were described as the basis for methods and strategies. Although the aim of these theories is to explain behavior or the process of behavior change, the methods and strategies that are derived from a.…”
Section: Rq2: On Which Theories or Empirical Data Are These Methods Amentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in the second column of Table 2, social learning (cognitive) theory (Patten et al, 2006;Patten et al, 2007;Suminski & Petosa, 2006), the transtheoretical model (Escoffery, McCormick, & Bateman, 2004), the informationmotivation-behavioral skills model (Barak & Fisher, 2003), self-regulation theory, and the theoretical fields of social support (Escoffery et al, 2004;Marks et al, 2006) and social norms (Saitz et al, 2007;Thombs et al, 2007) were described as the basis for methods and strategies. Although the aim of these theories is to explain behavior or the process of behavior change, the methods and strategies that are derived from a.…”
Section: Rq2: On Which Theories or Empirical Data Are These Methods Amentioning
confidence: 99%
“…Notably, there was no decline over 20 weeks . In another intervention, designed to deter alcohol use in residence halls, 61% visited the website the day after they consumed alcohol (Thombs et al, 2007).…”
Section: Rq4: What Are the Potential Effects Of Strategies To Facilitmentioning
confidence: 99%
“…If participants indicated they intended to drink more that night, they were asked to return to the research station after fi nishing their drinking for the night. Participants were not given their BrAC reading at night because of concerns that some participants might return to drinking if they perceived their level of intoxication to be low enough to continue drinking (Russ et al, 1988;Thombs et al, 2007) or to make a game of breath testing. They were provided an opportunity at the conclusion of the semester to obtain a list of their BrAC readings.…”
Section: Nighttime Measuresmentioning
confidence: 99%
“…Efforts to reduce heavy drinking among American college students still remain an important public health priority, despite numerous attempts to address the problem [4]. Previous researchers have demonstrated that heavy drinking is an important public health concern on university campuses; but, few researchers have compared universities with differing alcohol policies.…”
Section: Introductionmentioning
confidence: 97%
“…Although the implementation of alcohol policies is one strategy to reduce heavy drinking, it may not always be effective for numerous reasons such as lack of enforcement or the students' lack of awareness a policy exists [4]. The primary purpose of this study was to explore the relationship between the type of alcohol policy present on college campuses to the odds of heavy drinking among undergraduate students.…”
Section: Introductionmentioning
confidence: 98%